2023
DOI: 10.1111/nmo.14669
|View full text |Cite
|
Sign up to set email alerts
|

Adeno‐associated virus‐9 reverses delayed gastric emptying of solids in diabetic mice

Xiaojie Li,
Sihan Ji,
Gianluca Cipriani
et al.

Abstract: BackgroundGastroparesis is defined by delayed gastric emptying (GE) without obstruction. Studies suggest targeting heme oxygenase‐1 (HO1) may ameliorate diabetic gastroparesis. Upregulation of HO1 expression via interleukin‐10 (IL‐10) in the gastric muscularis propria is associated with reversal of delayed GE in diabetic NOD mice. IL‐10 activates the M2 cytoprotective phenotype of macrophages and induces expression of HO1 protein. Here, we assess delivery of HO1 by recombinant adeno‐associated viruses (AAVs) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(135 reference statements)
0
1
0
Order By: Relevance
“…Since HO1 expression levels are linked to the reversal of gastroparesis (29), further investigation into stimulating HO1 may yield additional therapeutic benefits. However, a recent study showed that adenovirus delivery of mouse Hmox1 yielded no significant results in relation to gastric emptying of solids, suggesting that HO1 is not the sole determining factor for gastroparesis reversal (45). Perhaps the immune response, particularly MMs, contributes more to GI diseases than HO1 alone.…”
Section: Disorders Of Gi Tract and Therapeutic Targetingmentioning
confidence: 99%
“…Since HO1 expression levels are linked to the reversal of gastroparesis (29), further investigation into stimulating HO1 may yield additional therapeutic benefits. However, a recent study showed that adenovirus delivery of mouse Hmox1 yielded no significant results in relation to gastric emptying of solids, suggesting that HO1 is not the sole determining factor for gastroparesis reversal (45). Perhaps the immune response, particularly MMs, contributes more to GI diseases than HO1 alone.…”
Section: Disorders Of Gi Tract and Therapeutic Targetingmentioning
confidence: 99%